2022
DOI: 10.1002/adma.202200270
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Modulation of Active Sites to Promote Electrocatalytic Oxygen Evolution

Abstract: kinetics in anodic electrode, that is, the four-electron coupled oxygen evolution reaction (OER). [1][2][3] At present, the benchmark OER catalysts are noble metalbased oxides such as IrO 2 and RuO 2 ; however, they are limited by scarcity and expensive cost. [4][5][6] Given this fact, the relatively inexpensive and performancepromising transition metal-based catalysts such as Fe/Co/Ni oxohydroxide and oxides are attracting increasing attention. [7][8][9][10][11][12] Ligand-modulation of Fe/Co/Ni-based metal-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
69
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(78 citation statements)
references
References 35 publications
1
69
0
Order By: Relevance
“…Porous coordination polymers (PCPs) or metal–organic frameworks (MOFs) are architected from the self-assembly of metal ions/clusters and organic ligands, which possess highly tunable structures, high specific surface areas, and abundantly accessible metal sites, enabling them to be attractive catalysts for both performance upgrades and mechanism studies. In particular, ultrathin two-dimensional (2D) PCP nanosheets are promising electrocatalysts due to their more exposed catalytic active sites and superior electrical conductivity. Recently, many investigations have confirmed that structural reconstruction can also occur in nanoscale PCPs to form more highly active species during the OER process. However, the main attention is focused on MASs to date, and the role of organic ligands in electrocatalysis is usually ignored. Hence, the quantitative correlation between the organic species, especially those containing heteroatoms, and OER activity remains enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…Porous coordination polymers (PCPs) or metal–organic frameworks (MOFs) are architected from the self-assembly of metal ions/clusters and organic ligands, which possess highly tunable structures, high specific surface areas, and abundantly accessible metal sites, enabling them to be attractive catalysts for both performance upgrades and mechanism studies. In particular, ultrathin two-dimensional (2D) PCP nanosheets are promising electrocatalysts due to their more exposed catalytic active sites and superior electrical conductivity. Recently, many investigations have confirmed that structural reconstruction can also occur in nanoscale PCPs to form more highly active species during the OER process. However, the main attention is focused on MASs to date, and the role of organic ligands in electrocatalysis is usually ignored. Hence, the quantitative correlation between the organic species, especially those containing heteroatoms, and OER activity remains enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the poor electronic conductivity, a feasible and highly efficient strategy is directly growing MOF catalysts on a conductive substrate. ,, Catalysts directly grown on a conductive substrate such as nickel foam (NF) and carbon cloth avoid the utilization of nonconductive binders that bury partial metal sites as well as enhance the electronic conductivity due to seamless contact between the catalyst and substrate. , Meanwhile, the mechanical stability will be pronouncedly promoted because self-supported electrocatalysts with strong binding force are less sensitive to the fast release of gas bubbles at high current density …”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39] However, in the structure of MOFs, the metal nodes are surrounded by organic linking groups, 40 which limits their catalytic activity and conductivity; 41 thereby, it is vital to construct these structures with a rational design. [42][43][44][45] In terms of macrostructure control, 46 Lou et al typically construct a unique core-shell structure through chemical etching methods and other methods, 47 which could provide a larger catalytic interface area, 48 thereby significantly improving the electrocatalytic performance. 49 Li et al used carbonization to precisely regulate Hofmann-type MOFs into different forms (including nanosheets, nanoflowers, 50 nanotubes and aggregates), which OER catalytic performance far exceeds that of commercial RuO 2 catalysts.…”
Section: Introductionmentioning
confidence: 99%